The Tradition of Martonggo in the Saur Matua Funeral Custom in the Toba Batak Community - YESSY OCTAVIANA (Journal of Oral Traditions, 2019)
The Tradition of Martonggo in the Saur Matua Funeral Custom in the Toba Batak Community